The intrinsic moral value of the human embryo: Holistic anthropology and the use of human embryos in research - Kerasidou, A (2014)
Using human embryos in research remains a controversial issue, especially in Christian bioethics. Although the official Catholic stance rejects human embryonic stem cell research, Christian thinkers T. Peters, K. Lebacqz and G. Bennett support it. They endorse the 14-day Rule and argue that ex vivo embryos lack moral worth. I examine and challenge the 14-day Rule and location argument (in vivo/ex vivo). I develop a theory of holistic anthropology and intrinsic moral value for human embryos. I conclude that intrinsic moral value is not equal to full moral value, and therefore use of embryos in biomedical research is morally permissible. © 2014 Center for Theology and the Natural Sciences.